(3TQM JPcQg GdWhSi aj GdgjFIs - (3GdMSf Hf eMeO GdfjSCHhQi hGdfXGe GdCYQLs; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3ef GdeYdhe Cf GdYdhe JJHGjf HMSH JHGjf ehVhYGJgG hJJeGjR ai GdhKGbg HMSH JeGjR ebOeJgG hGdYde GdPi fMf HUOOg hgh Yde gjFI GdBadGc s
(3BNQgG (B:s
(3bHd GdMeO CQMe GdQGMejf aEf GdCYeGd HGdfjGJ hHgG JLdH GdHQcGJ hJfGd GdOQLGJ hGdMeO ddeHOY s
(3GdcGFf ai GdbQf GdKGefs
(3cKjQ ef GdQShe GdgfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdadcs